Back to Basics: Re-embracing the Foundations of Clinical Ethics in Healthcare - Wyzynski, Daniel (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
PhD students, post-docs, and bioethics researchers are conducting nuanced research to develop advancements in the field, and this research offers valuable insights that can support the practice of bioethics. However, this research often does not address how much work is still needed to incorporate basic ethical principles into practice, from research oversight to applications within a clinic. Applying an ethical lens is often viewed as “time consuming” or “nice-to-have” in the professional field, rather than something that must be intrinsically built into every patient encounter. Much of the existing healthcare system fails to incorporate basic ethical deliberation into practice, causing avoidable conflict, tension, and mistrust. This paper cautions that there is a plethora of groundwork still needed before paving the way forward to advance the field of bioethics. The ground needs to be flat and the asphalt warm, otherwise the road we build will be cracked and unstable. To do this, new ethicists must passionately foster and promote elementary ethical deliberations across all domains of healthcare. We must strive to create spaces where all persons are comfortable sharing their concerns, values, and unique perspectives to best inform decision making. This paper synthesizes practical wisdom, emotional intelligence, and integrates surprising pragmatic lessons from the lived experience of an early career clinical ethicist.